2020
DOI: 10.1097/ccm.0000000000004133
|View full text |Cite
|
Sign up to set email alerts
|

Relative Hyperglycemia Is an Independent Determinant of In-Hospital Mortality in Patients With Critical Illness

Abstract: Objectives: To determine whether relative hyperglycemia was associated with in-hospital mortality in critically ill patients independent of other prognostic variables and whether this association is affected by background glycemia. Design: Prospective observational study. Setting: Mixed medical-surgical ICU in a metropolitan teaching hospital. Patients: From 2,61… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 44 publications
4
76
1
2
Order By: Relevance
“…Systemic corticosteroids could also induce hyperglycaemia, which was shown to be an independent risk factor for the prognosis of infection and critically ill patients [25][26][27]. We also found that median blood glucose level was higher during the use of systemic corticosteroids (The change of lymphocyte count and blood glucose level before, during and after corticosteroid use were shown in Supplementary Table 7).…”
Section: Systemic Corticosteroids May Have Worsened Prognosis By Promsupporting
confidence: 61%
“…Systemic corticosteroids could also induce hyperglycaemia, which was shown to be an independent risk factor for the prognosis of infection and critically ill patients [25][26][27]. We also found that median blood glucose level was higher during the use of systemic corticosteroids (The change of lymphocyte count and blood glucose level before, during and after corticosteroid use were shown in Supplementary Table 7).…”
Section: Systemic Corticosteroids May Have Worsened Prognosis By Promsupporting
confidence: 61%
“…Hyperglycemia is an independent risk factor for progression to critical cases and in-hospital deaths for both mild and severe patients. Intriguingly, stress hyperglycemia is an independent risk factor associated with worse outcomes among critically ill patients 90 . SARS-CoV-2 induced cytokine storm, and the direct infection of the pancreas leads to insulin resistance.…”
Section: Clinicopathological Mechanisms Of Fibrinolysis In Covid-19mentioning
confidence: 99%
“…3 Previous studies showed that stress hyperglycemia was an independent risk factor associated with worse outcomes among critically ill patients. 6 In addition, hypoglycemia may lead to cardiovascular events, also conferring a harmful effect on prognosis. 7 We therefore speculated that blood glucose levels may have predictive value on COVID-19 prognosis.…”
mentioning
confidence: 99%